PECULIARITIES OF ELECTRICAL NETWORK PARAMETERS ACCOUNTING WHEN USING MATHEMATICAL MODELS OF CURRENT CURVE SHAPE DISTORTION SOURCES - Нестерович, Віктор (SWorldJournal, 2024)
Mathematical models of distortion sources are used to estimate possible distortions of the shapes of current and voltage curves. The operating modes of distortion sources may depend on the parameters of the electric network and the parameters of its mode.